Injury rates in the national football league during the 2020 COVID-19 season - Platt, B. N.; Collofello, B.; Stockwell, N.; Jacobs, C. A.; Johnson, D. L.; Stone, A. V. (The Physician and Sportsmedicine, 2023)
Objectives The National Football League (NFL) altered the 2020 season due to the COVID-19 pandemic, which resulted in canceled preseason games and a dynamic regular season schedule to accommodate for canceled games. The purpose of this study was to evaluate if the disrupted training and preseason schedule lead to increased injury rates as seen in other professional sports. We hypothesized that the overall injury rate would be higher in the 2020 season compared to the 2018-2019 seasons and that this increase will affect all body regions equally.